New and validated high-rank syntaxa from Europe - Mucina, Ladislav; Dengler, Jürgen; Bergmeier, Erwin; Carni, Andraž; Dimopoulos, Panayotis; Jahn, Ralf; Matevski, Vlado (Lazaroa, 2010)
In the course of the compilation of a checklist of the high-rank syntaxa of Europe, it turned out that for several syntaxa no valid and legitimate names were available. With this contribution, we aim to solve some of the problems by publishing or validating seven syntaxon names (1 order, 5 alliances, 1 association) and by proposing a nomen novum for one illegitimate alliance name. The validations concern the Artemisio albi -Brometalia erecti (Festuco-Brometea; xerophytic basiphilous grasslands in subatlantic-submediterranean Europe), Dictamno albi-Ferulagion galbaniferae (Antherico ramosi-Geranietalia sanguinei, Trifolio-Geranietea sanguinei; xerophytic basiphilous forest-edge communities of the Balkans and the SE Alps), Euphorbio taurinensis-Geranion lucidi (Geranio-Cardaminetalia hirsutae, Stellarietea mediae; short-lived nitrophilous forest edge communities of Macedonia), and Gentianello amarellae-Helictotrichion pratensis (Brometalia erecti, Festuco-Brometea; meso-xerophytic basiphilous grasslands of NW Europe). A new alliance, the Alkanno baeticae-Pinion halepensis (Quercetalia ilicis, Quercetea ilicis; pine forests on ultramafic soils on the island of Euboea), is described to replace the nomen dubium Alyssion euboei. The Alkanno baeticae-Pinetum halepensis is described as a new association to serve as the type of the Alkanno-Pinion. Finally, within the Poterietalia spinosi (Cisto-Micromerietea julianae), the Helichryso barrelieri-Phagnalion graeci (phrygana communities on noncalcareous substrates in the south Aegean region) is described as new to science, and the nomen novum Hyperico olympici-Cistion cretici (phrygana communities on non-calcareous substrates in northern Greece) is proposed to replace the illegitimate Cistion orientale.